Selective Pre-concentration and Solid Phase Extraction of Trace Amounts of Copper(II) in Aqueous Samples Using Octadecyl Silica Membrane Disks - MOGHIMI, ALI; JAVAD POURSHARIFI, MOHAMAD (Asian Journal of Chemistry, 2010)
A new simple and reliable method for rapid and selective extraction and determination of trace levels of Cu2+ ion is developed. Copper ions are adsorbed quantitatively during passage of aqueous samples through octadecyl silica membrane disks modified with some recently synthesized mixed aza-thioether crowns containing 1,10-phenanthroline subunit. Almost all matrix elements were found to pass through the disk to drain. The retained Cu2+ ions are then stripped from the disk with a minimal amount of thiosulfate solution as eluent and subsequently measured by atomic absorption spectrometry. The proposed method permitted large enrichment factors of about 200 and higher. The limit of detection of the proposed method is 80 ng Cu2+ per 1000 mL. The method was applied to the recovery of Cu2+ ions from different synthetic and water samples.